An Enumeration Of Grasses of Kumaon Anti Gahwal Division and Dehra Dun District in Uttar Pradesh - Part-I - Misra, O. P.; Joshi, P. (Indian Forester, 1974)
The first instalment of an enumeration of grasses of 43 genera and 90 species covering sub-family Panicaceae collected in Kumaon, Garhwal Division and Dehradun District of Uttar Pradesh has been presented with short notes on each species on habit, habitat abundance, its soil binding and fodder properties, place of collection (District) wlth elevation above sea level and field book number of collection.